Enhancing grape juice with Lacticaseibacillus rhamnosus CWKu-12: Assessing probiotic viability, physicochemical changes, sensory characteristics, and quality kinetics throughout storage - Shaghayegh Echresh; Behrooz Alizadeh Behbahani; Fereshteh Falah; Mohammad Noshad; Salam A. Ibrahim (Applied Food Research, 2025)
Traditional non-dairy fermented beverages are produced worldwide. Fruit juices are popular with people of all ages and are seen as healthy and refreshing, leading to interest in creating probiotic functional beverages from them. ​The aim of this study was to prepare probiotic grape juices loaded with Lacticaseibacillus rhamnosus CWKu-12 and assess their physicochemical characteristics, probiotic load, and sensory acceptance during storage. In the next step, quality changes in grape juices during storage were described using various kinetics such as zero, first, or higher order. This strain was used at concentrations of 0, 1, and 2 % as a probiotic component in the grape juice model. The juice's pH, titratable acidity, color, probiotic load, and sensory acceptability were assessed during 21 days of storage at 4 and 25 °C. The pH and acidity of the probiotic grape juices were kept constant during storage at 4 °C. At the end of the storage period, the juice containing 2 % probiotic and stored at 4 °C had the highest viable cells (7.92 log CFU/mL). Moreover, grape juices that had been cold-stored and added probiotics had the highest level of sensory acceptance. The findings indicated that zero-order reaction models best represented the quality indices of the juice, with high R2 values and low RMSE. As a result, for lactose intolerant individuals, vegetarians, and people who are allergic to dairy products, this may be used as a nutraceutical with health-promoting benefits.